KAJIAN BUILD OPERATE TRANSFER (BOT) DALAM HUKUM PERJANJIAN DI INDONESIA - Thamrin, Husni (STIH Awang Long Samarinda, 2017)
Build operate transfer (BOT) is a contract or agreement closely related to land or land as an object of development in the agreement. This resulted in the BOT contract can not be separated from the provisions of legislation related to land. Nevertheless, the land provisions in question are the provisions that govern the land that leads to prosperity. Basically, BOT, also called build operate transfer system, is a concept whereby the project is built at full cost from private companies as well as some private companies or cooperation with State-Owned Enterprises and once built is operated by contractors, then after the operation phase is complete the transfer project to the government as the project owner and landowner in accordance with the BOT agreement. The scope of the BOT agreement is that it can be viewed from 2 interests, which are seen in the interests of investors and the interests of the government.